Biocides and Novel Antimicrobial Agents for the Mitigation of Coronaviruses - Dev Kumar, Govindaraj; Mishra, Abhinav; Dunn, Laurel; Townsend, Anna; Oguadinma, Ikechukwu Chukwuma; Bright, Kelly R.; Gerba, Charles P. (Frontiers in Microbiology, 2020)
In December, 2019, a strange new pneumonia of unknown cause was reported to the Chinese WHO Country Office. A cluster of these cases had appeared in Wuhan, a city in the Hubei Province of China. These infections were found to be caused by a new coronavirus which was given the name “2019 novel coronavirus” (2019-nCoV). It was later renamed “severe acute respiratory syndrome coronavirus 2,” or SARS-CoV-2 by the International Committee on Taxonomy of Viruses on February 11, 2020. It was named SARS-CoV-2 because the virus closely related to the coronavirus which caused the SARS outbreak in 2002 (SARS-CoV). This virus has spread worldwide since then and has resulted in more than two million cases of illnesses as of April 13, 2020, and these cases are icreasing exponentially. The aim of this review is to provide information about a range of alternative biocides effective in eliminating or reducing the presence of coronaviruses from fomites, skin, oral mucosa, air and food contact surfaces. Specifically, we focused on the effects of alcohols, povidone iodine, quaternary ammonium compounds, hydrogen peroxide, sodium hypochlorite, peroxyacetic acid, ammonia, chlorne dioxide, ozone, ultraviolet light, metals, and plant-based antimicrobials. This review highlights the differences in the resistance or susceptibility of different strains of coronaviruses to antimicrobial agents.